Effect of capsaicin supplementation on repeated sprinting performance - Opheim, M. N.; Rankin, J. W. (The Journal of Strength and Conditioning Research, 2012)
Performance in many team sports is partially dependent on the ability to perform repeatedly at high intensity. Previous research demonstrates that capsaicin (CAP) has physiological and metabolic effects that could influence exercise performance and inflammation. The purpose of this study was to investigate the influence of CAP on performance of and the interleukin-6 (IL-6) response to repeated sprints. Nineteen healthy male experienced athletes, age 18-30 years, participated in a placebo (PCB)-controlled, crossover study. During 1 trial, they consumed 3 g/d cayenne (25.8 mg·d-1 CAP) and the other a PCB for days. Directly after the supplementation period, they completed a repeated sprint test (RST) consisting of 15 30-m maximal effort sprints on 35-second intervals with sprint times measured via an electronic dual-beam timing system. Fasted blood draws for IL-6 were taken at baseline before supplementation, 45 minute pre-RST, and immediately post-RST. Rate of perceived exertion (RPE), muscle soreness (MS), and gastrointestinal distress (GD) for 5 symptom subscales were measured 1-minute pretest, during, posttest, and 1-minute posttest. The MS was additionally measured for 3-day posttest. Relative to the PCB, CAP significantly increased the sum of ratings of GD symptoms by 6.3-fold. There was no difference between treatments in fastest or mean sprint time, fatigue, IL-6 response, RPE, or MS. In summary, CAP did not influence repeated sprint performance or the IL-6 response but caused substantial GD. The CAP is not recommended for athletes involved in repeated sprinting.